The growth performance and nutritive value of three varieties of guinea grass at two different cutting interval - Ismail, Muhamad Khairul Anwar (2015)
A study was conducted to measure the growth performance and nutritive value of 3 different varieties of Panicum maximum cv. (Common guinea grass, Purple guinea grass, Mambosa guinea grass) at 2 different cutting interval 28 days and 35 days.The grasses were sampled at 28 days and 35 days of age and analyzed for dry matter yield (DM yield), neutral detergent fiber (NDF), acid detergent fiber (ADF), acid detergent lignin (ADL) and crude protein (CP). There was significant difference (P<0.05) in height, leaf percentage, ASH and NDF among the varieties. There was no significant difference (P>0.05) on DM yield, CP, ADF and ADL among the 3 varieties. The study also concluded that among of 3 varieties of Panicum maximum, Purple guinea and Mambosa guinea was superior in term of DM yield, plant height, and CP. There was highly significant different (P<0.01) on DM yield, height of grass, leaf percentage, CP, ADF and ADL between 28 days and 35 days cutting interval. The study showed that the most suitable cutting interval for the Panicum maximum grass was at 28 days in term of growth performance and nutritive value. Also overall there was no interaction affect on the growth performance and nutritive value between the cutting interval and among of the three varieties of guinea grass.